Determinan Minat Berwirausaha Mahasiswa - Lala Latifa Annisa Aprilia; Nurabiah Nurabiah (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze the influence of e-commerce, entrepreneurial knowledge, accounting information systems, and motivation on the entrepreneurial interest of accounting students. The research employed a quantitative method with an associative approach. The sample consisted of 113 students from universities in Mataram City who had completed courses in Accounting Information Systems and Entrepreneurship, selected through purposive sampling. The results show that e-commerce (t = 0.413; p = 0.679) and entrepreneurial knowledge (t = 0.408; p = 0.684) do not have a significant effect on entrepreneurial interest. Conversely, accounting information systems (t = 8.380; p = 0.000) and motivation (t = 2.706; p = 0.007) have a significant effect. The coefficient of determination (R²) of 0.589 indicates that 58.9% of the variation in entrepreneurial interest can be explained by the four independent variables in the model. Several indicators were found to be invalid and are recommended not to be used in future research, including: for the e-commerce variable—honesty and responsibility, physical and mental endurance, and orientation and readiness to take risks; for the entrepreneurial knowledge variable—indicators related to marketing, banking, and the internet; for the accounting information systems variable—creative thinking, idea generation, and business opportunity analysis; and for the motivation variable—punctuality, reliability, profit, freedom, personal dreams, and independence.